2018
DOI: 10.18203/2349-2902.isj20181389
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic ductal adenocarcinoma in a Moroccan population: analysis of six years experience

Abstract: Background: Few studies have been done to investigate pancreatic cancer in Morocco. Therefore, the aim of our study was to describe the epidemiological, clinical and therapeutic features of pancreatic ductal adenocarcinoma in Moroccan population.Methods: Author retrospectively reviewed the medical data of pancreatic ductal adenocarcinoma patients presented to the Medical Oncology Department of the Military Hospital Moulay Ismail in Meknes, Morocco, from January 2011 to December 2016.Results: The study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These data are broadly consistent with those of Ferlay et al (2021) [ 13 ], who reported that the frequency of patients with pancreatic tumors is approximately the same between males and females. Although previous studies by researchers at the Military Hospital Moulay Ismail in Meknes, Morocco have shown that males are at higher risk of developing the disease than females [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data are broadly consistent with those of Ferlay et al (2021) [ 13 ], who reported that the frequency of patients with pancreatic tumors is approximately the same between males and females. Although previous studies by researchers at the Military Hospital Moulay Ismail in Meknes, Morocco have shown that males are at higher risk of developing the disease than females [ 14 ].…”
Section: Discussionmentioning
confidence: 99%